Prognostic impact of sarcopenia on 5-year overall and progression-free survival in lung cancer patients: a prospective cohort study - Zhao, Ting; Li, Xin-qi; Shi, Zhan; Zhang, Chao-bao; Zhu, Ying-gang (Frontiers in Nutrition, 2026)
BackgroundSarcopenia is increasingly recognized as a critical prognostic factor in cancer patients, particularly in lung cancer, However, currently the relationship between Sarcopenia and lung cancer prognosis was primarily assessed using imaging modalities such as CT scans and its impact on outcomes in Chinese lung cancer patients, assessed using comprehensive Asian diagnostic criteria, remains underexplored. This study aimed to evaluate the association between Sarcopenia and tumor prognosis and outcome in lung cancer patients.MethodsA prospective cohort of 403 lung cancer patients admitted to Huadong Hospital (2020–2025) was analyzed. Sarcopenia was diagnosed using Asian Working Group for Sarcopenia (AWGS) criteria, combining muscle mass (bioelectrical impedance analysis), handgrip strength, and gait speed. Survival outcomes (overall survival [OS] and progression-free survival [PFS]) were compared between sarcopenic and non-sarcopenic groups using Kaplan–Meier and univariate and multivariate Cox regression analyses were used to identify independent predictors of OS and PFS.ResultsSarcopenia was identified in 43.2% of patients (174/403). Compared with non-sarcopenic patients, sarcopenic patients had significantly shorter median OS (13.2 vs. 43.3 months; p < 0.001) and PFS (11.5 vs. 25.4 months; p < 0.001). At baseline, sarcopenic patients were older (74.3 ± 7.7 vs. 71.0 ± 8.2 years, p < 0.001), had lower BMI (20.5 ± 2.9 vs. 23.5 ± 2.9 kg/m2, p < 0.001), poorer ECOG PS (1.4 ± 1.1 vs. 0.9 ± 0.8, p < 0.001), higher NRS-2002 (3.7 ± 1.6 vs. 2.6 ± 1.2, p < 0.001), lower handgrip strength (23.4 ± 7.1 vs. 30.8 ± 7.8 kg, p < 0.001), and slower walking speed (0.7 ± 0.3 vs. 1.0 ± 0.2 m/s, p < 0.001). In multivariable Cox regression, sarcopenia independently predicted worse OS (HR 2.33, 95% CI 1.64–3.33, p < 0.001) and PFS (HR 1.70, 95% CI 1.26–2.28, p < 0.001), with consistent trends across most subgroups. Only low BMI (OS p = 0.59; PFS p = 0.693), squamous cell carcinoma and other histology (OS p = 0.14; PFS p = 0.056), and I-II tumor stage (OS p = 0.098; PFS p = 0.682)showed no significant associations, while in patients with high body fat percentage the association with OS was not significant (p = 0.115) but remained significant for PFS (HR 1.68, 95% CI 1.03–2.72, p = 0.036).ConclusionSarcopenia is associated with reduced overall survival time and progression-free survival in lung cancer patients. Sarcopenia is an independent predictor of poor survival particularly in specific high-risk subgroups. When assessing for sarcopenia it is crucial to include assessment of muscle function in evaluating the prognosis of lung cancer.